Improving the Creativity of Senior High School Teachers and Students in Learning History in Klaten District - Insiwi Febriary Setiasih; Sawitri Pri Prabawati; Isnaini Wijaya Wardani (Budapest International Research and Critics University, 2020)
In the current age of information technology, learning history and culture has its own challenges. The material is really complex that the teaching model and the restricted teaching hours require teachers to deliver the material more creatively. High school students are on the other hand, in a context of immense self-actualization. This, they need to be able to understand history with a new approach. Film is an appealing medium because it uses the language of images and dialog to encourage them to listen. History learning needs to improve in order to meet the aims outlined in the curriculum in the midst of the rapid flow of modernization with sophisticated information communication media. The right media for that are documentary films with the re-recording and reconstruction process. It is therefore necessary to undertake an activity aimed at equipping teachers with film-based teaching techniques, as well as increasing the creativity of high school students in Klaten to identify and record historical phenomena. The location of the service was chosen because of the fascinating historical and cultural potential that Klaten Regency has to record and reproduce. It is certainly not easy to process documentary films, especially historical themes. Skills are required to trace both oral and written sources that can be accounted for as material for the storyline of the movie. Students can practice historical techniques here as well as directly understand historical details and periodicity. The next stage is the professional method of filming, reviewing, editing, and screening films to be viewed in a forum.